THE SOCIAL PARTNERSHIP MODEL IN UZBEKISTAN AND ITS FEATURES - Ibodulla KUNGIROV (Western European Studies, 2024)
Social partnership is determined by the stage of its development, the characteristics of the social partnership system of each country and the level of its social orientation. Social partnership serves to maintain a balance in the interests of society, to harmonize the interests of state and non-state organizations. That is, it implements the sociopolitical relations of citizens between state and non-state organizations in the social life of society on the basis of democratic principles. In Uzbekistan, the advanced experience of developed foreign countries is being studied in detail in the implementation of social partnership relations in socio-political life. The social partnership model in our country is aimed at ensuring the rights, interests and freedoms of all segments of social life. The social partnership model implemented in Uzbekistan is based on the advanced methods of models of foreign countries that have reached the stage of development. However, in our country, the existing social partnership is being implemented in a way that is specific to us and is based on our own needs and requirements.
Keywords: social partnership; social difference; community interests